Cataract increases the risk of peripheral artery occlusive disease: A nationwide population-based cohort study with propensity score. (1st October 2016) - Hu, Wei-Syun; Lin, Cheng-Li; Huang, Chih-Yang; Chang, Shih-Sheng; Chang, Kuan-Cheng
Abstract: Purpose: We conducted this study to evaluate the risk of peripheral artery occlusive disease (PAOD) among patients with cataracts. Methods: We analyzed the data from Taiwan National Health Insurance Research Database. Study participants were classified into the cataract group and the non-cataract group between 2000 and 2010. All patients were observed from the index year until PAOD diagnosis, loss to follow up, or the end of 2011. Both study groups were 1:1 matching based upon a propensity score. We used a cox proportional hazards regression model to assess the hazard ratio (HR) and 95% confidence interval (CI) of PAOD for the cataract cohort compared with the non-cataract cohort. Results: After adjustment for age, sex and comorbidities, the risk of PAOD was significantly higher in the cataract cohort [adjusted HR (aHR) = 1.48, 95% CI = 1.38-1.58] than the non-cataract cohort. Conclusions: We found that patients with cataracts had a 1.48-fold increased risk of developing PAOD compared to the non-cataract patients.